Challenging Legal Injustice against Children in Incest Cases: A Progressive and Islamic Human Rights Approach - Ulvi Rohmatul Musyayyadah; Lukman Santoso; Achmad Baihaqi (De Jure: Jurnal Hukum dan Syari'ah, 2025)
Illegitimate children born from incest present complex issues in civil law, particularly concerning their legal status and the protection of their rights. The main legal problem concerns the position of the biological father. Under Islamic law, the biological father has no legal relationship of lineage, guardianship, or inheritance with the child. However, from a moral, constitutional, and human rights perspective, the father still bears responsibility for fulfilling the child’s basic rights. This study examines the legal consequences and obligations of biological fathers toward illegitimate children using the perspectives of Progressive Law and Islamic Human Rights. The research employs a normative legal method, focusing on Article 283 of the Civil Code, which prohibits the recognition of illegitimate children. This provision is analyzed in relation to the Child Protection Law, the Human Rights Law, the International Covenant on Civil and Political Rights, and other relevant regulations. In addition, conceptual and philosophical approaches are used to reinterpret rigid legal norms by emphasizing justice, humanity, and social reality. The study finds that recognition of illegitimate children by their biological fathers may be permitted to the extent that it ensures the fulfillment of the child’s fundamental rights, such as financial support, education, and health care. However, recognition should not extend to lineage, inheritance, or guardianship, in order to uphold the principle of hifz al-nasl (protection of lineage). These limitations are not discriminatory but aim to harmonize child protection with the principles of Islamic law. Furthermore, responsibility for protecting children does not rest solely on parents; the state and society also have a duty to ensure that all children receive equal protection. This research offers a legal reconstruction that bridges Islamic law and human rights, providing a normative basis for child protection policies consistent with maqāṣid al-sharīʿah.